Implementation of Three Dimensional Virtual Reality on Android Based At Tanwir Umsida Tower: Implementasi Tiga Dimensi Virtual Reality Pada Tower At-Tanwir Umsida Berbasis Android - Agung Novianto, Putra; Dijaya, Rohman (Universitas Muhammadiyah Sidoarjo, 2024)
In the current digital era, many technologies are being developed, one of which is virtual reality or VR technology,VR can be used for various problems in the current era including the introduction of an item, building, etc. At theUniversity of Muhammadiyah Sidoarjo (UMSIDA) itself, the 23 floor At-Tanwir Tower building will be built whichlater have many facilities for educators, students or the community. Of course, an introduction to the current era isneeded, namely VR, with the creation of the Android based At-Tanwir VR Tower, it is hoped that it will be easy torecognize the outdoor/indoor environment of the building and be able to introduce the building to the widercommunity. Later, VR users can look around and explore outside and inside the building from the parking lot, grasses,classrooms, auditorium, theater stage, cafeteria and the observatory room, all of which are three dimensional.